FY2014-FY2016 Medium-Term Budget. (Policy Papers; Policy Paper ;, 2013)
The proposed FY 14-16 Medium-Term Budget was formulated within the Fund's strengthened strategic planning framework and seeks to align the allocation of resources to the delivery of institutional priorities. Despite the additional resources that have been provided to meet crisis demands, crisis related work and overall work pressures remain elevated. At the same time, available resources are not being fully utilized. Therefore, the budget strategy-instead of asking for further additional resources-is geared toward making more efficient use of existing resources to reduce work pressures and meet new demands.